Case Report on Congenital Heart Disease with Miliary Tuberculosis (Journal of Pharmaceutical Negative Results, 2022)
Background: Miliary tuberculosis is the widespread dissemination of Mycobacterium tuberculosis. It is the result of hematogenous dissemination and is characterized by extensive miliary mottling of lungs and involvement of the spleen, liver, and other tissues. It may be found as pulmonary type or septicemic type or meningitic type. Coarctation of the Aorta is a distinct narrowing or long segment hypoplasia of the aortic arch, usually distal to the subclavian artery. The narrow aortic lumen may exist as preductal or postductal obstruction which depends upon the position of the obstruction about the ductus arteriosus. The lesion obstructs blood flow through the aorta, resulting in increased pressure and effort of the left ventricle. Patient presentation: We are presenting an 8-year-old male child who visited the pediatric outpatient unit with the symptoms of fever, cough, and increased work of breathing, he was admitted to PICU. He was a known case of congenital heart disease. He was diagnosed to have congenital heart disease at the age of 3 years when he was admitted to the hospital due to the bluish coloration of his palms and soles. He had a fever (100 degrees F), cough, and increased work of breathing for 15 days during normal daily activities. The patient had undergone a 2-D Echo showing a parachute mitral valve. He was treated with antibiotics and maintained saturation on O2 by CPAP. Symptoms such as Respiratory distress and cough are relieved after maintaining saturation O2 and medications. Conclusion: Coarctation of the Aorta is typically present at birth (congenital heart defect). Mild to severe symptoms are possible. The illness might not be discovered until an adult. Coarctation of the Aorta frequently coexists with other congenital cardiac abnormalities. There are different methods employed for the treatment of CoA in adults, including surgical or percutaneous balloon angioplasty with or without stent placement, and medical therapy. Miliary Tuberculosis is one type of tuberculosis. This condition is rare in people with a normal immune system. It’s more common in people whose immune system isn’t working right. This is called being immunocompromised. Often your lungs, bone marrow, and liver are affected by miliary TB, but it can also spread to the lining of your heart, your spinal cord and brain, and other parts of your body. Treatment strategies in a patient with Miliary tuberculosis require the same treatment as Tuberculosis (Antibiotics).